Effect of length of storage and chemical additives on the nutritive value and starch degradability of reconstituted corn grain silage - Oliveira, Késia da Silva (2020)
The rehydration and ensiling of dry corn grain are processing methods capable to improve the starch digestibility by breakdown of the protein matrix that surrounds starch granules, allowing the access by the ruminal bacteria. This processing method can result in greater feed efficiency of dairy cows by decreasing dry matter intake without altering milk production. Chemical additives can control ethanol production by inhibiting yeasts development, improve aerobic stability and decreasing the dry matter losses in grain silage. Synthetic surfactants, such as polyoxyethylene (20) sorbitan monooleate, have lipophilic (hydrocarbon chain) and hydrophilic (polar head) properties in the same molecule, and are widely applied in the food industry to stabilize immiscible substances, as water-oil interfaces, interacting with food matrices and modifying its structure through physical mechanisms. The objective of this study was to evaluate the effect of treatment with propionic acid, polysorbate 80 or propionic acid and polysorbate 80 mixture on reconstituted corn grain silage stored for 15, 30, or 60 d on the chemical composition, ruminal in situ degradability, and silage conservation. Dry ground corn was mixed with distilled water manually to achieve a moisture content of 35%. A total of 177.2 kg of dry ground corn, were rehydrated and then ensiled in 5-L plastic buckets sealed with plastic lids. Four piles (44.3 kg of dry grain per pile) were treated with polysorbate 80 (2 L/t) (POL), propionic acid 28% (2 L/t) (PRO), MycoflakeTM (2 L/t) (MYC) or nothing (CON). The effect of length of storage (15, 30, or 60 d), was also evaluated and combined in a factorial arrangement with the additives effect. Four replicates were used per treatment. Data were analyzed using the MIXED procedure of SAS. We evaluated the chemical composition, pH, lactic acid content, volatile fatty acids, ethanol, ammonia nitrogen, soluble protein, dry matter losses, aerobic stability, kernel fraction particle size distribution, geometric mean particle size (GMPS) and surface area of the corn grain, and ruminal in situ starch and dry matter degradability. The DM content was higher at 15 and 30 d than at 60 d of ensiling. The crude protein (CP) content decreased over time and was lower in silages treated with Mycoflake compared to the other treatments. There was an interaction between additive and storage length for soluble protein content, where at 15 d of ensiling, POL had lower soluble protein content than CON and MYC, after 30 d it had lower soluble protein content than MYC, and no differences were observed among treatments after 60 d. Ammonia nitrogen content was higher for 30 and 60 d of storage than 15 d, 53.2 and 59.4%, respectively. The length of storage and treatment changed the kernel particle size distribution. There was a decreased amount of material retained on the bottom pan at 60 d of storage compared with 15 and 30 d. The MYC had lower percentage of grain held at 1.7 and 1.18-mm sieves compared to the other treatments. At 0.6-mm sieve, the PRO and MYC decreased the amount of particles kept regarding CON and POL. However, the percentage of material held at pan was higher for MYC than other treatments. It was observed an increase in GMPS at silages stored for 60 d and with the MYC there was a reduction compared with CON and POL. A decreased in surface area occurred in silages stored for 60 d and the MYC presented a higher surface area. There was an interaction between additive and storage length for pH. After 30 d of ensiling only PRO had lower pH than CON, but after 60 d all silages treated with additives had lower pH than CON. The lactic acid concentration was higher at 30 d in comparison with 15 d of storage. At 30 d, the POL and PRO had lower ethanol concentration than CON, and at 60 d all treatments except CON controlled ethanol concentration. The propionic acid concentration was higher in silages treated with additives that contained propionic acid (PRO and MYC) than for CON and POL at all lengths of storage analyzed. All silages stored for 15 d had low and similar butyric acid concentration, but at 30 and 60 d of storage, the untreated silages had higher butyric acid concentration than treated silages. Aerobic stability increased from 15 to 30 d, but was the same at 30 and 60 d. At 15 d of storage, the treatments PRO and MYC were efficient to decrease the DM losses. At 60 d all treated silages presented lower DM loss than CON. The length of storage increased the ruminal in situ degradability of starch and DM. The MYC increased the DM degradability at 12 h of incubation compared to POL. In conclusion, increasing the storage time of reconstituted corn grain silages improved the ruminal degradability of starch and DM. The Mycoflake increased the availability of nutrients and Polysorbate 80 can be a potential antimicrobial agent in corn grain silages. Further studies are needed to better determine the effect of a combination of chemical additive and polysorbates in corn grain silages.